Freedom of Thought, Conscience, and Religion - Đukić, Dalibor (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
This chapter analyses the protection of freedom of thought, conscience, and religion under the European Convention on Human Rights, with a special focus on violations of religious freedom in Central and Eastern European states. In general, states have been granted a wide margin of appreciation in regulating their relationship with religions, including the legal status of religious organisations.Most countries in the region have adopted a cooperationist model of state-religion relations, which appears to be consistent with their obligations under Article 9. However, registration systems in some countries breach the Convention, as they create disparities in the treatment of religious organisations and violate the communal aspect of religious freedom. On the other hand, individuals have faced challenges in manifesting their religion in special institutional settings, such as hospitals and prisons. The chapter argues that while a significant portion of judgments in which the European Court of Human Rights has identified violations of Article 9 involves countries in Central and Eastern Europe, there is no evidence of systematic violations of the right to manifest one’s religion in this region.Keywords: History of religious freedom protection, Freedom of thought and conscience, Freedom of religion or belief, European Convention on Human Rights, European Court of Human Rights, Central and Eastern European Countries, Recognition of religious organisations